Institutional governance and responsiveness to antimicrobial resistance: a qualitative study of Australian hospital executives - Alex Broom; Jennifer Broom; Katherine Kenny; Pamela Konecny; Jeffrey J. Post (BMJ Open)
Objectives Despite escalating antimicrobial resistance (AMR), implementing effective antimicrobial optimisation within healthcare settings has been hampered by institutional impediments. This study sought to examine, from a hospital management and governance perspective, why healthcare providers may find it challenging to enact changes needed to address rising AMR.Design Semistructured qualitative interviews around their experiences of antimicrobial stewardship (AMS) and responsiveness to the requirement for optimisation. Data were analysed using the framework approach.Setting Two metropolitan tertiary-referral hospitals in Australia.Participants Twenty hospital managers and executives from the organisational level of department head and above, spanning a range of professional backgrounds and in both clinical and non-clinical roles, and different professional streams were represented.Results Thematic analysis demonstrated three key domains which managers and executives describe, and which might function to delimit institutional responsiveness to present and future AMR solutions. First, the primacy of ‘political’ priorities. AMR was perceived as a secondary priority, overshadowed by political priorities determined beyond the hospital by state health departments/ministries and election cycles. Second, the limits of accreditation as a mechanism for change. Hospital accreditation processes and regulatory structures were not sufficient to induce efficacious AMS. Third, a culture of acute problem ‘solving’ rather than future proofing. A culture of reactivity was described across government and healthcare institutions, precluding longer term objectives, like addressing the AMR crisis.Conclusion There are dynamics between political and health service institutions, as well as enduring governance norms, that may significantly shape capacity to enact AMS and respond to AMR. Until these issues are addressed, and the field moves beyond individual behaviour modification models, antimicrobial misuse will likely continue, and stewardship is likely to have a limited impact.